The presumption of innocence under anti-terrorism laws: A comparative study of the laws in Malaysia and England and Wales / Lazarus Jansen Xavier Benny - Lazarus Jansen , Xavier Benny (2006)
This paper is about the presumption of innocence under anti-terrorism Jaws and is undertaken in a comparative manner, examining the laws of Malaysia, and England and Wales, hence, the influence of English common law in our legal system. The presumption of innocence is regarded as the cornerstone of the criminal justice system and operates throughout the criminal process. Thus, it is observed that the right to be presumed innocent f01ms an effective theoretical safeguard which reflects due process of Jaw.